The Effects of Placemaking on The Pekanbaru City Park - Agung Rizki Adhal A; Revianto B. Santosa (Syntax Corporation Indonesia, 2025)
Placemaking is the process of transforming an area into a place with a feeling of place by taking into account the community's social requirements and psychology. The culture and environment of a location can also impact the space created. Public space design must be well-planned in order to increase the quality of metropolitan environments. The municipal park is one of the public areas that should be evaluated. However, not every park is open to the public. this research was made in the hope to be able to identify the reasons why there are not that many visitors here even though, this is one of the only green open space areas in Pekanbaru. The results of this study suggest that the physical aspects of Pekanbaru City Park suit some needs of some users. The condition and sanitation of both the facilities and park itself are also needed as soon as possible. . Because of the smell from the water in the middle, many avoid it and go to the outer side and corner.